Correlation of Visual Distraction Method Toward Pain Reduction in Preschool Children at The Emergency Installation - Dian, Dian Vita Sari; fatmawati, fatmawati; Alhuda, Alhuda (Babali Nursing Research, 2023)
Background: Child's reaction in overcoming the crisis is influenced by the level of age, experience of the process being sick and treated, the support system available, and coping skills in dealing with stress. Preschool-age children is very difficult to understand the invasive procedures that can cause pain such as during IV insertion. When a child is hospitalized usually the child will be given an infusion. The infusion is done in order to gets the fulfillment of nutrition, fluids, and medicines. Yet, when the infusion installed on children, they can feel pain. The aims of study to determine the relationship between the visual distraction method and the reduction of pain in infusion preschool children. Methods: The population in this study was pre-school children who were treated at the Emergency Room. The sampling technique used Accidental Sampling with a total sample of 105 people. Results: The research results obtained with a confidence level of 95% (α 0.05), it is known that the p value or Asymp value Sig. (2-sided) which is 0.001 means that the P value is 0.001 ≤ 0.05, this shows that there is a significant relationship between the Visual Distraction Method and the Pain Reduction Method in Infusion for Pre-School Children in the Emergency Room at Cut Meutia hospital of North Aceh. Conclusion: The use of nonpharmacological techniques has a significant impact on pain management in children. Various non-pharmacological measures that can be performed include using the distraction method. Audiovisual distraction therapy is thought to help release endorphins which have a function to reduce stress and pain.